Analysis Implementation Of Accounting Information Systems In Supporting Internal Control Of Rahn (Pawn) Financing At Darussalam Syariah Pawnship Banda Aceh - Evriyenni, Evriyenni; Ramadhani, Natasya; Hasnita, Nevi; Yulianti, Rahmah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Accounting Information Systems (AIS) play a vital role in strengthening the governance of Islamic financial institutions, particularly in ensuring transparency, accountability, and compliance with sharia principles. This study aims to analyze the implementation of AIS in supporting internal control of Rahn (pawn) financing at Pawnship Syariah Darussalam Banda Aceh. The study employs a descriptive qualitative method; with data collected through interviews, observations, and documentation. The results indicate that AIS is integrated into all operational stages of Rahn financing, from customer data recording, collateral appraisal, and financing disbursement to repayment. Features such as audit trails, access authorization, automatic notifications, and real-time reporting were found to enhance internal control. However, challenges remain, including data entry errors and limited human resource competencies. The study concludes that AIS implementation at Pawnship Syariah Darussalam Banda Aceh contributes significantly to internal control effectiveness, though improvements in staff training and system development are still required.